2014
DOI: 10.1016/j.econlet.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Does venture capital really foster innovation?

Abstract: D Do oe es s v ve en nt tu ur re e c ca ap pi it ta al l r re ea al ll ly y f fo os st te er r i in nn no ov va at ti io on n? ?" " A An na a P Pa au ul la a F Fa ar ri ia a N Na at tá ál li ia a B Ba ar rb bo os sa a NIPE WP 03/ 2013 " "D Do oe es s v ve en nt tu ur re e c ca ap pi it ta al l r re ea al ll ly y f fo os st te er r i in nn no ov va at ti io on n? ?" " A An na a P Pa au ul la a F Fa ar ri ia a N Na at tá ál li ia a B Ba ar rb bo os sa a N NI IP PE E *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…Besides providing funds, these active investors usually add value to their invested companies by engaging in monitoring, recruiting executives and directors, formulating strategies, and helping with further fund-raising activities. It has been demonstrated theoretically and empirically that venture capitalists play an important role in funded companies ' general performance and market value (Lerner, 1995;Kortum and Lerner, 2000;Hellmann and Puri, 2002;Kaplan and Str ömberg, 2004;Guo and Jiang, 2013;Faria and Barbosa, 2014).…”
mentioning
confidence: 98%
“…Besides providing funds, these active investors usually add value to their invested companies by engaging in monitoring, recruiting executives and directors, formulating strategies, and helping with further fund-raising activities. It has been demonstrated theoretically and empirically that venture capitalists play an important role in funded companies ' general performance and market value (Lerner, 1995;Kortum and Lerner, 2000;Hellmann and Puri, 2002;Kaplan and Str ömberg, 2004;Guo and Jiang, 2013;Faria and Barbosa, 2014).…”
mentioning
confidence: 98%
“…In the past decades, North American and European countries actively sought to increase the size of their venture capital markets 6–10. The levels of venture capital available to Canadian life sciences companies have more than doubled from 2001 to 2010 11.…”
Section: Venture Capital and New Medical Technologiesmentioning
confidence: 99%
“…Examining panel data of 17 European Union countries, Faria and Barbosa6 found that venture capitalists are “more willing to support innovation only after the initial and more uncertain stage of technology development has been overcome.” This tendency partly explains why the Horizon 2020 Programme protected up to €320.14 million in 2014 to help innovative firms to gain access to various types of risk financing 5. To foster the growth of technology-based ventures, venture capital typically steps in after entrepreneurs have fleshed out their core innovative idea with the financial support of governments, relatives and ‘angels’ (eg, wealthy individuals who finance entrepreneurial activities) 3.…”
Section: Venture Capital and New Medical Technologiesmentioning
confidence: 99%
“…In this study, number of patent applications at European Patent Office (EPO) was used as frequency of patent. The number of patent applications were used as measurement instead of patent grants in line with previous contributions (Cho & Lee, 2013;Faria & Barbosa, 2014). However the data of 21 countries was obtained from EUROSTAT.…”
Section: Patentsmentioning
confidence: 99%